2018
DOI: 10.3390/ijms19082249
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Cellular Accumulation of Pt-Based Chemotherapeutic Drugs

Abstract: Cisplatin, carboplatin, and oxaliplatin are Pt-based drugs used in the chemotherapeutic eradication of cancer cells. Although most cancer patient cells initially respond well to the treatment, the clinical effectiveness declines over time as the cancer cells develop resistance to the drugs. The Pt-based drugs are accumulated via membrane-bound transporters, translocated to the nucleus, where they trigger various intracellular cell death programs through DNA interaction. Here we illustrate how resistance to Pt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…It should be taken into account that clinically relevant oxaliplatin concentrations in mice might be below the detection limit of the presented technique and necessitate novel strategies for investigating the corresponding metabolites involved, e.g., the application of Pt(IV) analogues. 23,47,48 In SW480 cells, the metal core distribution of oxaliplatin is similar to cisplatin (Fig. 2B, Fig.…”
Section: Discussionmentioning
confidence: 79%
“…It should be taken into account that clinically relevant oxaliplatin concentrations in mice might be below the detection limit of the presented technique and necessitate novel strategies for investigating the corresponding metabolites involved, e.g., the application of Pt(IV) analogues. 23,47,48 In SW480 cells, the metal core distribution of oxaliplatin is similar to cisplatin (Fig. 2B, Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The analysis of Cu exporters, ATP7A and ATP7B, confirmed that Ctr1 is the major determinant for cisplatin accumulation in yeast and mice cells [ 105 ]. But recent studies suggest that the transporters involved in the cellular accumulation of cisplatin are classified as; (i) Cu transporters: Ctr1, Ctr2, ATP7A, ATP7B; (ii) ABC transporter: ATOX1; (iii) organic cation transporter: OCT1; (iv) multidrug and toxin extrusion family members: MATE; (v) volume sensitive, the volume-regulated anion channel proteins: VRAC (LRRC8A/D-containing) [ 106 ]. Leucine-rich repeat-containing protein 8 (LRRC8) encoded by genes LRRC8A/D is the subunit of heteromer protein VRAC [ 107 , 108 ].…”
Section: The Role Of Cu In Cancermentioning
confidence: 99%
“…Since the discovery of the LRRC8 gene family, there has been a revitalization of interest in the physiological and pathophysiological roles VRAC plays in different cell types and tissues. By disrupting the expression of LRRC8A using knock‐down or knockout techniques, new roles of VRAC in drug uptake (Lambert & Sorensen, ), sperm development (Luck, Puchkov, Ullrich, & Jentsch, ), adipocyte biology (Zhang et al, ), pain (Wang et al, ), and insulin secretion (Stuhlmann et al, ) have recently been described. Mongin and colleagues demonstrated using siRNA against LRRC8A that VRACs are essential for swelling‐induced release of the excitatory amino acid glutamate in vitro (Hyzinski‐Garcia, Rudkouskaya, & Mongin, ; Schober, Wilson, & Mongin, ).…”
Section: Introductionmentioning
confidence: 99%